Interaction of human neutrophils with Trichomonas vaginalis protozoan highlights lactoferrin secretion - Wei-Hung Cheng; Ruei-Min Chen; Seow-Chin Ong; Yuan-Ming Yeh; Po-Jung Huang; Chi-Ching Lee (Journal of Microbiology, Immunology and Infection)
Background: Neutrophils are vital constituents of the immune response in the vaginal environment, playing a pivotal role in the defense against trichomoniasis. Earlier studies have shown that Trichomonas vaginalis (T. vaginalis) can release leukotriene B4 (LTB4), a molecule that attracts and activates neutrophils. Additionally, secretory products from this parasite can induce the production of interleukin-8 (IL-8) in mast cells and neutrophils, which further recruits neutrophils to the infection site. The precise reasons behind T. vaginalis actively promoting interaction between parasites and neutrophils rather than inhibiting the inflammatory response remain unclear. Results: In this study, we collected conditioned medium to elucidate the intricate dynamics between T. vaginalis and human neutrophils. We conducted a comprehensive profiling of soluble excretory/secretory proteins (ESPs), identifying 192 protein spots, of which 94 were successfully characterized through mass spectrometry analysis. Notably, the majority of induced ESPs from co-cultivation exhibited consistency with the trichomonad and neutrophil standalone groups, except for lactoferrin, which was observed exclusively following the interaction between neutrophils and T. vaginalis. The secretion of lactoferrin was determined to be a contact-dependent process. It was interesting to identify the ability of the iron-loaded lactoferrin to extend the survival time of T. vaginalis under iron-deficient conditions. Conclusions: This study represents the first to identify the origin of lactoferrin during T. vaginalis infection, shedding light on the potential reason for T. vaginalis's ability to attract neutrophils to the infection site: the acquisition of the iron source, lactoferrin.